E. coli in tropical urban rivers : a case study of the Sungai Gombak basin - Zainudin, Zaki; Rahman, Norazah; Jamal, Parveen; Al-Khatib, Ma'an Fahmi Rashid (2014)
The primary study area is Sg. Gombak, a river that flows through the mostly urbanized state of Selangor and transcends the capital of Malaysia, Kuala Lumpur. The study aims to characterize E. coli, organics and nutrients on the main stem of the river and its tributaries of Sg. Batu and Sg. Kerayong. There were 28 identified spatial sampling stations throughout the basin. The results on the upper reaches of Sg. Gombak showed E. coli levels ranged between 100 – 400 cfu/100mL. The levels increased and remained between 11,000 cfu/100mL to 18,000 cfu/100 mL downstream upon receiving sewage effluent and other pollution sources. This was comparable to Sg. Batu. Conditions were even worse in Sg. Kerayong as E. coli levels were in excess of 140,000 cfu/100 mL. Ambient temperature increase in excess of 30°C with a ∆T rise of 3 to 4°C appeared to result in some decrement of E. coli; at 0.08/°C for Sg. Gombak and 0.20/°C for Sg. Batu, albeit this only occurred at single spatial points in both rivers. Variation in BOD5, NH3-N and NO3-N did not appear to significantly influence bacterial count in the basin. The study results also showed for the water to be deemed suitable for skin contact, a removal efficiency of at least 92% has to be achieved, which in turn, translated to a die-off period of at least two hours.